Home delivery among pregnant women with ANC follow-up in Ethiopia; Evidence from the 2019 Ethiopia mini demographic and health survey - Tariku, Mandaras; Enyew, Daniel Berhanie; Tusa, Biruk Shalmeno; Weldesenbet, Adisu Birhanu; Bahiru, Nebiyu (Frontiers in Public Health, 2022)
Background: Maternal mortality has remained an international public health problem although it is decreasing in recent years. Developing countries particularly Sub-Saharan African countries bears the high burden of maternal deaths. There was no study conducted to assess prevalence and associated factors of home delivery among women in Ethiopia on ANC follow up nationally. Therefore, this study was conducted to assess the magnitude and associated factors of home delivery in Ethiopia. Methods: Secondary data analysis was carried out using Ethiopian Mini Demography and Health Survey (EMDHS 2019). A total weighted sample of 2,143 women who had antenatal care follow up during pregnancy was incorporated in the study. In a generalized linear mixed model (GLMM), Adjusted Odds Ratio (AOR) with a 95% Confidence Interval (CI) and p-value < 0.05 were declared as associated factors of home delivery. Results: The prevalence of home delivery was 31.27 % [95% CI: 29.34%, 33.27%] among women who had antenatal care follow up in Ethiopia. Attended higher education [AOR=0.27; 95% CI: (0.13, 0.54)], rural resident [AOR=2.15; 95% CI: (1.19, 3.90)], richest in the wealth index [AOR=0.18; 95% CI: (0.10, 0.32)], had adequate ANC follow up [AOR=0.25; 95% CI: (0.13, 0.51)] and being in third trimesters [AOR=0.64; 95% CI: (0.49, 0.83)] during first ANC visit were significantly associated factors of home deliver. Conclusion: Near to one-third of women in Ethiopia have delivered their babies at home even if they had an ANC follow up. Educational status, place of residence, wealth index, timing of first antenatal check and adequate ANC visit has shown significant association with home delivery. Therefore, focused intervention packages need to be implemented at all levels of the health care system in Ethiopia to improve health seeking behaviors of women who have ANC follow up to have delivery in health care institutions. While doing so, special attention should be given for poor, uneducated and rural dweller women. Key word: Home delivery, ANC, Ethiopia mini demography survey